2010
DOI: 10.1299/jmmp.4.1131
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Order Infinite Element Method for Stress Analysis of Elastic Bodies with Singularities

Abstract: Structural analysis problems are traditionally solved using the Finite Element Method (FEM). However, when the structure of interest contains discontinuities such as cracks or re-entrant corners, a large number of elements are required to accurately reproduce the stress characteristics in the region of the discontinuities. As a result, the FEM method requires a large storage space and has a slow convergence speed. It has been shown that the Infinite Element Method (IEM) overcomes these limitations and provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Liu et al [18,19] have combined the IEM with the FEM to solve static linear problems and have continuously extended equations from 2D to 3D. Liu et al [20] further derived a high-order IEM equation for analyzing various 2D elastic static problems; they compared their results with those of the traditional loworder IEM and with analytical solutions provided in the literature. eir findings revealed that the results obtained using their method were more accurate than those obtained using the low-order IEM and were in good agreement with the analytical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [18,19] have combined the IEM with the FEM to solve static linear problems and have continuously extended equations from 2D to 3D. Liu et al [20] further derived a high-order IEM equation for analyzing various 2D elastic static problems; they compared their results with those of the traditional loworder IEM and with analytical solutions provided in the literature. eir findings revealed that the results obtained using their method were more accurate than those obtained using the low-order IEM and were in good agreement with the analytical solutions.…”
Section: Introductionmentioning
confidence: 99%